THE DEBUT PRAISED, BUT NOT AWARDED... AND WHAT NEXT? - Machala, Lubomír (Bohemica Olomucensia, 2020)
The first part of the article analyzes and interprets the prose debut of Lucie Faulerová Lapači prachu in order to present the qualities and assets of this work, which should have been taken into account by various Czech literary awards. The second part of the article points out that the author's second prose called Smrtholka seems to be the text less artistically succesful and convincing than Lapači prachu - despite the fact it shares a number of elements, features and procedures with the first work, and despite the fact it is definitely one of the superior works in the context of Czech contemporary literature.
Keywords: Lucie Faulerová; first and second prose; literary awards; strengths; weaknesses